PENINGKATAN HASIL BELAJAR BAHASA INDONESIA PESERTA DIDIK SUB TEMA 1 AKU DAN CITA-CITAKU MELALUI PENERAPAN METODE RESITASI KELAS IV SD NEGERI 100950 AEK TOLONG KABUPATEN PADANG LAWAS UTARA - Harahap, Martua; Nasution, Sartika Rati Asmara; Nurzanna, Nurzanna; Sabri, Sabri; Siregar, Royhanun (Program Studi Pendidikan Guru Sekolah Dasar Fakultas Pendidikan Ilmu Pengetahuan Sosial dan Bahasa Institut Pendidikan Tapanuli Selatan, 2025)
This study aimed to describe achievement improvement in the cognitive domain of students Indonesian of sub-theme 1” I and my dream” through applying recitation method at fourth grade of SD Negeri 100950 Aek Tolong, North Padang Lawas Regency. This study uses CAR (Classroom Action Research) which includes two cycle and the subjects consist of 18 students. The data collection technique used observation and tests. The data was analyzed by using quantitative and qualitative analysis. The first cycle shows the average of students achievement is 64.38 (poor category), 10 students is completeness (55.56%) and 8 students is not completeness. Furthermore the second cycle shows the average students achievement is 84.38 (good category), 16 students is completeness (88.89%) and 2 students is not completeness.